Polygamy in Hermeneutics and Maqashid Sharia Approach - Yurizka Syahdani; Nur Azizah (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
Polygamy is defined as the practice of a man who marries more than one woman, but with a maximum limit of four wives. The restriction on the number of wives in Islam is based on the consideration that more than four wives are considered deviant from the moral and beneficial principles regulated in sharia. This research uses the library research method, which is a research that focuses on written data sources, with the research results that polygamy is a form of emergency solution that is given in certain social conditions and in accordance with the purpose of sharia' if carried out in accordance with the principles of Islamic sharia.